Real-Time Cost Awareness in Surgical Disposables: A Multispecialty Pre-Post Trial. - Poder, Thomas G.; Harris, Philippe; Têtu, Maxime; Mondoloni, Pascal; Vernelus, Cathy; Mignault, Alexandre; Liberman, Moishe (Journal of Medical Systems, 2025)
This study was conducted to demonstrate the impact of a software-based cost awareness intervention on the reduction of cost of surgical disposables used in thoracic, gynecological, colorectal and plastic surgery. We used a prospective, non-randomized, pre-post trial in video assisted thoracic surgery (VATS) lobectomy, total laparoscopic hysterectomy, laparoscopic low anterior resection, and deep inferior epigastric perforator (DIEP) flap breast reconstruction. Overall, 775 cases performed between February 2021 and August 2023 were included in the study, 521 for VATS lobectomy (control n = 164), 127 for laparoscopic total hysterectomy (control n = 19), 48 for laparoscopic colorectal surgery (control n = 8), and 79 for DIEP flap breast reconstruction (control n = 53). Average age was 63 years with 67% female and average BMI of 27.57 kg/m2. Most patients had a cancer diagnosis (83%) and average ASA score was 2.46. The control period consisted of collecting baseline product usage and cost data without visibility to the clinical teams. During the intervention period, real-time post-operative reports detailing the disposable products used and their cost per intervention were sent out to surgeons. Overall adjusted cost savings were estimated at $631.34 or -24.5% [95%CI: -737.89; -524.78]. The main driver for cost savings was VATS lobectomy (-$793.61), followed by laparoscopic colorectal resections (-$520.93), DIEP flap breast reconstruction (-$198), and laparoscopic total hysterectomies (-$87.11) for the adjusted sample sizes. A computer-vision capture software provides real-time cost awareness on disposable products to clinical teams and is an effective tool to reduce the cost of disposable supplies in various surgical settings.